Consensus guidelines for the diagnosis and management of patients with classic hairy cell leukemia - Grever, Michael R.; Ho, Anthony Dick; Zenz, Thorsten (Blood, 2017)
Hairy cell leukemia is an uncommon hematologic malignancy characterized by pancytopenia and marked susceptibility to infection. Tremendous progress in the management of patients with this disease has resulted in high response rates and improved survival, yet relapse and an appropriate approach to re-treatment present continuing areas for research. The disease and its effective treatment are associated with immunosuppression. As more patients are being treated with alternative programs, comparison of results will require general agreement on definitions of response, relapse, and methods of determining minimal residual disease. The development of internationally accepted, reproducible criteria is of paramount importance in evaluating and comparing clinical trials to provide optimal care. Despite the success achieved in managing these patients, continued participation in available clinical trials both in the front-line and particularly in the relapse setting is highly recommended. The Hairy Cell Leukemia Foundation convened an international conference to provide common definitions and structure to guide current management. There is substantial opportunity for continued research in this disease. In addition to the importance of optimizing the prevention and management of the serious risk of infection, organized evaluations of minimal residual disease and treatment at relapse offer ample opportunities for clinical research. Finally, a scholarly evaluation of quality of life in the increasing number of survivors of this now manageable, chronic illness merits further study. The development of consensus guidelines for this disease offers a framework for continued enhancement of the outcome for patients.